An Analysis of Halva Price and Demand Dynamics by Granger Causality - Dilek, Serkan; Kesgingöz, Hayrettin; Işik, Sefa (Elsevier BV, 2016)
Abstract In this study causality relation between the price and demand of Kastamonu Halva has been examined. We did our analysis by using the data series of Kastamonu Halva demand and prices between 1989-2014 periods. We obtained demand and price data by conducting survey to Halva producers in Kastamonu. In our study to test whether there is causality between prices and demand we used Granger Causality test after applying ADF unit root test. As a result of our analysis we found that price is Granger cause of Kastamonu Halva demand and it affects demand in negative way. This result is coherent to previous studies and classical demand rule of economics. At the same time, it is surprisingly found that income is not Granger cause of Kastamonu Halva which is opposing to economic theory.
Keywords: 8. Economic growth